A Novel Seven-Day Abbreviated Two-Stage Exchange Arthroplasty with Intra-Articular Antibiotic Irrigation for Chronic Periprosthetic Joint Infection of the Knee: A Case Report - Nicolas S Piuzzi; Ignacio Pasqualini; Shujaa T Khan; Bryan D Springer; Brian C De Beaubien (Journal of Orthopaedic Case Reports)
Introduction: The current standard for treating chronic periprosthetic joint infection (PJI) in North America, a two-stage exchange arthroplasty, has success rates of 65–90% but involves prolonged interstage periods, increased morbidity, and a high 5-years mortality rate of up to 25%. These limitations have driven research into alternative approaches, such as intra-articular antibiotic (IAA) irrigation, which uses a specialized titanium spacer for localized antibiotic delivery over a 7-day period. Case Report: A 53-year-old male with chronic PJI of the left knee underwent a novel rapid two-stage exchange arthroplasty using an IAA irrigation system. The first stage involved implant removal and placement of a specialized antibiotic delivery IAA device. During the 7-day interstage period, high-concentration local antibiotics (tobramycin and vancomycin) were administered. The second stage, performed 1 week later, included reimplantation with a total stabilized revision knee system. At 1-year post-surgery, the patient demonstrated excellent functional recovery, pain-free mobility, and no signs of recurrent infection. Conclusion: This case illustrates the potential of IAA in managing chronic PJI, offering rapid reimplantation and effective infection control. While promising, larger studies are needed to establish long-term efficacy and cost-effectiveness of this innovative approach.